Rancang Bangun Aplikasi Panduan Pariwisata di Kabupaten Banyuwangi Mobile Berbasis Android - Wira Shilviana Hanum; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Tourism is a very important sector for the development of a region and tourism is one of the means of promotion to introduce the beauty of nature and the uniqueness of the culture in the area. Including for Banyuwangi Regency which is one of the regencies in East Java Province. This regency has many objects or tourist destinations which are a mainstay and the development of the tourism sector must be accompanied by the development of information technology. Smartphone is one form of technological development and one of the most popular smartphone technology bases based on its operating system is Android.The use of android smartphones in the development of the world of tourism in the information technology era is important for the public and tourists to have knowledge about objects or tourist destinations that will be targeted. In supporting the needs of the tourism information system in Banyuwangi Regency, an Android-based application was created. An application on an android smartphone that suits the needs of travelers equipped with interesting features. This application contains information about tourist objects that are equipped with visual media such as pictures, videos and Google Maps facilities to facilitate in finding tourist locations that will be addressed by the public and tourists.